Concussion Guidelines Step 2: Evidence for Subtype Classification. Issue 1 (21st August 2019) - Lumba-Brown, Angela; Teramoto, Masaru; Bloom, O Josh; Brody, David; Chesnutt, James; Clugston, James R; Collins, Michael; Gioia, Gerard; Kontos, Anthony; Lal, Avtar; Sills, Allen; Ghajar, Jamshid
Abstract: BACKGROUND: Concussion is a heterogeneous mild traumatic brain injury (mTBI) characterized by a variety of symptoms, clinical presentations, and recovery trajectories. By thematically classifying the most common concussive clinical presentations into concussion subtypes (cognitive, ocular-motor, headache/migraine, vestibular, and anxiety/mood) and associated conditions (cervical strain and sleep disturbance), we derive useful definitions amenable to future targeted treatments. OBJECTIVE: To use evidence-based methodology to characterize the 5 concussion subtypes and 2 associated conditions and report their prevalence in acute concussion patients as compared to baseline or controls within 3 d of injury. METHODS: A multidisciplinary expert workgroup was established to define the most common concussion subtypes and their associated conditions and select clinical questions related to prevalence and recovery. A literature search was conducted from January 1, 1990 to November 1, 2017. Two experts abstracted study characteristics and results independently for each article selected for inclusion. A third expert adjudicated disagreements. Separate meta-analyses were conducted to do the following: 1) examine the prevalence of each subtype/associated condition in concussion patients using a proportion, 2) assess subtype/associated conditions in concussion compared to baseline/uninjured controls using a prevalence ratio, and 3) compare the differences in symptom scores between concussion subtypes and uninjured/baseline controls using a standardized mean difference (SMD). RESULTS: The most prevalent concussion subtypes for pediatric and adult populations were headache/migraine (0.52; 95% CI = 0.37, 0.67) and cognitive (0.40; 95% CI = 0.25, 0.55), respectively. In pediatric patients, the prevalence of the vestibular subtype was also high (0.50; 95% CI = 0.40, 0.60). Adult patients were 4.4, 2.9, and 1.7 times more likely to demonstrate cognitive, vestibular, and anxiety/mood subtypes, respectively, as compared with their controls ( P  < .05). Children and adults with concussion showed significantly more cognitive symptoms than their respective controls (SMD = 0.66 and 0.24; P  < .001). Furthermore, ocular-motor in adult patients (SMD = 0.72; P  < .001) and vestibular symptoms in both pediatric and adult patients (SMD = 0.18 and 0.36; P  < .05) were significantly worse in concussion patients than in controls. CONCLUSION: Five concussion subtypes with varying prevalence within 3 d following injury are commonly seen clinically and identifiable upon systematic literature review. Sleep disturbance, a concussion-associated condition, is also common. There was insufficient information available for analysis of cervical strain. A comprehensive acute concussion assessment defines and characterizes the injury and, therefore, should incorporate evaluations of all 5 subtypes and associated conditions.